Optimizing Affiliate Business Promotion through Social Media Marketing, Influencer Marketing, and Lead Generation: A Moderation-Mediation Model - Iqra Sarfraz; Sobia Hassan; Maryam Gull (NUML International Journal of Business & Management, 2025)
Modern e-businesses have introduced new marketing strategies to compete in today’s market. Within this framework, affiliate businesses have emerged, offering significant opportunities for business owners to engage, enhance marketing efforts, boost profitability, and earn a substantial return on investment. This research aims to determine the influence of social media marketing activities on promoting affiliate businesses. Affiliate businesses enable individuals and organisations to promote products and services on behalf of others and earn commissions based on the leads they generate. Lead generation facilitates the conversion of social media marketing efforts into leads for affiliate businesses. This study examines the role of social media marketing activities in enhancing affiliate business promotion, with lead generation acting as a mediator. Additionally, influencer marketing serves as a moderator, influencing the relationship between social media marketing activities and lead generation. By collaborating with influencers on social media platforms, businesses can effectively reach a wider audience and increase the credibility of their affiliate services. This study employs a quantitative approach, follows a deductive strategy, and utilizes a purposive sampling technique. The sample consisted of 210 respondents actively engaged in an affiliate business. Smart-PLS was used to analyze the data. The results indicate that social media marketing activities, lead generation, and influencer marketing have a significant influence on affiliate business promotion. The findings suggest that affiliate marketers should utilize social media in a manner tailored to their platform and employ systematic approaches to generate leads. Additionally, the study found that collaboration with influencers enhances the credibility and effectiveness of advertisements in prompting consumer action.